The importance of dental counseling to prevent dental caries in school-age children at SD X Bekasi - Nourmayansa Vidya Anggraini; Serri Hutahaean (Universitas Muhammadiyah Magelang, 2023)
Dental health problems still receive less attention. One of the targets that must be considered in maintaining dental health is the school-age children. This service activity aims to raise awareness of healthy living, build habits to be able to apply how to brush their teeth properly in school-age children in everyday life, and train them to always maintain healthy teeth and mouth. Community service methods are carried out with health counseling, demonstrations and simulations. Participants were asked to fill in pre and posttest to find out changes in knowledge, attitudes and behavior. This program succeeded in increasing children's knowledge, attitudes and behavior related to dental health. It is hoped that this program will continue to be sustainable in order to remind school-age children to take health care, especially teeth, so that optimal dental health is achieved.